Pengaruh Fraksi Volume Serat terhadap Kekuatan Tarik Serat Daun Nanas dan Serbuk Cangkang Kerang Dengan Matrik Resin Epoxy - Fernanda Aditya; Sutrisno; Wahidin Nuriana; Muhammad Hasan Basri (Jurnal Engine: Energi, Manufaktur, dan Material, 2026)
Natural fiber reinforced composite materials are increasingly being developed as an alternative to metal due to their lightweight, strong, and environmentally friendly properties. This study used pineapple leaf fiber and shell powder with an epoxy matrix to determine the optimal composition to improve the tensile properties of the composite. The purpose of this study was to determine how much fiber influences the tensile strength of pineapple leaf fiber and shell powder with an epoxy resin matrix. Specimens were made using the hand lay-up method and alkalization treatment, with a fixed composition of 60% epoxy, while the content of pineapple leaf fiber and shell powder varied from 10%; 15%; 20%; 25%; 30%. Tensile tests were carried out in accordance with ASTM D638. The results showed that the composition of 60% epoxy, 25% pineapple leaf fiber, and 15% shell powder produced the highest tensile strength of 20.80 MPa and the highest elastic modulus of 2029.4 MPa, while the highest strain value of 0.0228 was obtained in the composition of 60% epoxy, 15% pineapple leaf fiber, and 25% shell powder. In general, pineapple leaf fiber contributes to increasing tensile strength, while shell powder increases material stiffness through a more even stress distribution.